Interleaving Syntax and Postsyntax: Spellout before Syntactic Movement. (15th March 2019) - Martinović, Martina
Abstract: This article explores the proposal that a phase can be at least partially spelled out and then subsequently accessed by heads from a higher phase. I provide morphological evidence for this claim, by looking at examples in which a morphological (i.e., postsyntactic) process feeds a later narrowly syntactic one. Main evidence comes from the interaction between syntactic head movement and postsyntactic affixation in the Niger‐Congo language Wolof, which confirms an important prediction of the analysis. Namely, if a postsyntactic process can feed a syntactic one, we also expect the postsyntactic process to be bled if the structural conditions for its application are not met, resulting in surface opacity effects. This is precisely what we find in Wolof, where the past‐tense morpheme oon is postsyntactically affixed onto the verb in a particular structural configuration and carried along with it to C but is stranded by the verb below C if the structural requirements for its affixation are not met.